New Technological Revolution and Energy Requirements - Filippov, Sergey (Foresight and STI Governance, 2018)
The new technological revolution is radically changing the shape and development conditions of the world energy industry. The increase in demand for energy, alongside with changes in its structure, require the development of breakthrough technologies and the supply of new energy resources, which is associated with significant costs. To optimize them, a timely anticipation of the expected socio-economic changes and future energy requirements is needed. This paper analyzes the possible implications of the new technological revolution for the global and domestic energy industries. It evaluates current and prospective trends, such as changes in energy consumption due to growing demand from the service sector and households while reducing the needs of large-scale industry, digitalization, the formation of “mobile”, “portable” energy, and so on. Russia will maintain demand for a centralized energy supply while increasing the demand for distributed generation and cogeneration with the involvement of renewable energy sources, smart grid technologies, and other solutions. The current structure of the national fuel and energy complex is vulnerable to the large-scale electrification of transport and decarbonization of world energy.